Experimental study: coolant viscosity's impact on Inconel 600's surface roughness measured using a refractometer - Pujo Leksonowati, Nur Fitria; Pamungkas, Nurman; Manurung, Meilani Mandalena; Batubara, Ninda Hardina; Widiastuti, Hanifah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This paper presents an experimental study on the impact of coolant viscosity on the surface roughness of Inconel 600 material processed using a lathe. This research employs sequential experimental methods, encompassing a coolant viscosity test, specimen machining with a lathe, and surface roughness test. The standard for the roughness grade number is defined by ISO 1302. The study effectively demonstrates the use of a refractometer as a reliable and practical alternative for determining coolant quality in % Brix units, which strongly correlates with coolant viscosity. The research findings reveal that an increase in coolant viscosity results in a smoother surface roughness of the workpiece, while a decrease leads to an increase in surface roughness. Specifically, the average viscosity of 8%, 10%, and 13% Brix coolant results in an average surface roughness of Ra 11.83 Î¼m, Ra 10.09 Î¼m, and Ra 7.23 Î¼m, respectively. The average roughness grade number based on this study is N9 - N10. However, the study also identifies the need for further mathematical calculations to establish a link between coolant concentration, % Brix, and coolant viscosity. This opens up an intriguing avenue for future research and holds the potential to significantly enhance our understanding of the relationship between these variables.